Implementing the Refugee Resettlement Process: Diverging Objectives, Interdependencies and Power Relations - Schneider, Hanna (Frontiers in Political Science, 2021)
Refugee resettlement is implemented by many different national and international stakeholders who operate in different locations and on the basis of sometimes diverging objectives. The implementation of the resettlement process has thus been characterized as multi-level governance, with resettlement stakeholders coordinating and negotiating the selection of refugees for resettlement. Still, literature on the implementation of refugee resettlement has remained very limited and has mainly focused on one specific stakeholder or stage of the process. In addition, a common conceptualization of the different stages is currently missing in academic literature. To address this research gap, the article proposes a common terminology of all stages of the resettlement process. Highlighting the diversity of resettlement programs, the article relies on a comparative case study of the German resettlement and humanitarian admission programs from Jordan and Turkey. By drawing on the concept of multi-level governance, the article examines diverging objectives and interdependencies between resettlement stakeholders, such as UNHCR and resettlement countries. As a result, the article argues that the increasing emphasis on national selection criteria by resettlement countries, including Germany, puts resettlement countries even more in the center of decision-making authority–in contrast to a diffusion of power that characterizes multi-level governance.